PENANGANAN RUSAKNYA BAGASI PENUMPANG DI BANDAR UDARA ADISUTJIPTO YOGYAKARTA DALAM PERSPEKTIF HUKUM ISLAM (Studi Kasus Pada Divisi Unit Lost And Found di Bandara Adisutjipto Yogyakarta) - Hidayatullah; Munawaroh, Syayidatul (Universitas Nahdlatul Ulama Al Ghazali Cilacap, 2021)
This study discusses the law on handling damaged passenger baggage at Yogyakarta Adisutjipto airport. The problems that will be discussed in this research are: 1. What is the form of handling damaged passenger baggage at Yogyakarta Adisutjipto Airport? 2. What is the view of Islamic law on the handling of damaged passenger baggage at Yogyakarta Adisutjipto Airport? The research method uses field research (field research) with qualitative descriptive methods. Meanwhile, the approach uses an empirical/sociological juridical research approach, strengthened by the arguments of the Qur'an and Hadith. Primary data in this study were taken from interviews with the object of research, and supported by secondary data in the form of documents, books and journals that support this research. From this research, it can be concluded that the handling of passenger baggage problems that are lost, damaged, or found in thedivision of lost and found PT. Angkasa Semesta services have been handled according to the specified procedure and in accordance with the baggage problem. While the view of Islamic law in handling damaged passenger baggage is that it is in accordance with Islamic law and the Responsibilities of Air Transport Carriers and for lost baggage that is not recorded in the system, the company will not receive compensation.